ANALISIS KONSEKUENSI PUBLIKASI MASALAH RUMAH TANGGA DI MEDIA SOSIAL DENGAN PERSPEKTIF SAD ADZ-DZARI’AH - M. Aulia Urrahman (STIS Darussalam Bermi, 2024)
This study aims to elucidate the consequences of publicizing household problems on social media and to analyze them from the perspective of Sad adz-Dzari’ah. By utilizing a literature review approach, this qualitative and descriptive-analytical research is based on the Sad adz-Dzari’ah analytical framework. The findings indicate that publicizing household problems on social media can provide temporary catharsis for individuals experiencing stress or emotional pressure. However, the study also reveals that the negative impacts of such actions often outweigh the benefits. Negative criticism and comments from social media users can amplify feelings of shame, low self-esteem, and anxiety. Moreover, the implications of publicizing household problems on social media extend far beyond the individual. Interpersonal relationships within the family and with close friends can be strained, leading to a breakdown in trust and escalating conflicts. Socially, such publications can tarnish the family’s reputation and impact the social and professional status of its members. Legally, the published information can be used as evidence in proceedings like divorce or child custody cases, potentially leading to injustice. Ethically, this action breaches privacy and the integrity of family relationships, exposing personal issues without the consent of all parties involved. The Sad adz-Dzari’ah analysis further suggests that publicizing household problems on social media should be avoided due to the long-term harm that is difficult to erase, such as negative impacts on children’s emotional and psychological development and the family’s reputation. This study recommends that individuals consider the long-term consequences and seek more constructive and private alternatives for resolving household issues, such as counselling or family mediation, to protect psychological and emotional well-being and maintain the harmony and integrity of family relationships.